Paradigm shift; the emergence of arbitral forum shopping in CPEC investment disputes. Issue 3 (15th November 2019) - Idrees, Rao Qasim; Shapiee, Rohimi; Ahamat, Haniff
Abstract : Purpose: The phenomena of arbitral forum shopping to resolve a commercial investment dispute is still under development and more complicated in many states. However, for Pakistan, it seems in an evolutionary phase, where the country is struggling hard to adopt the best practice of dispute resolution through forum shopping clauses. This struggle is even more inflated with huge Chinese investment through China Pakistan economic corridor (CPEC) projects in Pakistan, which come alongside with commercial investment disputes. For this purpose, the current treaty or contract-based system between China and Pakistan and litigation based domestic civil court structure look obsolete, hence, appear to require reinstatement of forum shopping clauses under concerned treaties or contracts for CPEC investment-related issues. Design/methodology/approach: The authors choose a legal research method. The research design is a comparative analysis between CPEC contracts and dispute resolution mechanism between China and Pakistan and also the domestic civil court's litigation system. This analysis selected by the authors due to inefficient bilateral investment arrangements and efficient resolution of future commercial disputes in CPEC. While the international arbitration system is included in the assessment were particular in the time and space context. The comparison comprises on dispute resolution clauses in free trade agreement (FTA) and bilateral investment treaties (BIT) between China and Pakistan and the system of resolving disputes by CPEC clauses. Findings: The authors finds that in the absence of CPEC forum shopping clause under dispute resolution system, Pakistan is highly at risk to lose foreign investors, and therefore, set back the goal of long term economic sustainability in the region. However, China has already made its investment policies safer with establishing three international commercial courts (also referred to as Belt and Road courts), one in Xi'an for the land-based Silk Road Economic Belt, one in Shenzhen for the Maritime Silk Road and one in Beijing that will serve as the headquarters. These courts will be offering litigation, arbitration and mediation services. According to one view, China aims to have all belt and road initiative (BRI) disputes resolved by these courts. This makes Pakistan position more awkward and needs proactive measures, as CPEC investment is based on Pakistan foreign direct investment policies and legal structure. Therefore, it will be complicated and less favourable for Pakistan to deal with such cases under Chinese Courts. Originality/value: The paper's primary contribution is finding that comprehensive analysis of alternative dispute resolution mechanism between China and Pakistan over CPEC investment is inevitable. A socio-legal research combine with an examination of Singapore International Commercial Court functions and mechanism and CPEC plans further contributes to ascertain the best model of the settlement of commercial disputes under investments in Pakistan. This research paper anticipates future economic and legal problems, which Pakistan may encounter.